Dietary supplementation with Arthrospira platensis in tambatinga (♀Colossoma macropomum × ♂Piaractus brachypomus) - Ribeiro, Pedro; Leite, Lorena; Quaresma, Fabrízia; Farias, Wladimir Ronald; Sampaio, Alexandre (Revista Ciência Agronômica, 2019)
The aim of this study was to evaluate different levels of dietary supplementation with dried Arthrospira platensis meal during the breeding season of the tambatinga hybrid, using zootechnical performance, haematological parameters and percent composition of the fillet, and by measuring the parameters of water quality. Experimental breeding lasted 64 days. The fry, with an initial weight of 3.56 ± 0.02 g, received diets with two levels of supplementation (20 and 40%) and one control (commercial feed, without the addition of A. platensis meal). The water quality parameters over safe limits were total ammonia (NH3), nitrite (NO2-), and nitrate (NO3-), which increased as the level of supplementation increased, but did not cause any mortalities. The best zootechnical results for final weight, weight gain, feed conversion and feed efficiency were obtained with the treatments that included the addition of 20 and 40% meal. The highest levels of crude protein (CP) in the fillets were found in the treatments with added supplement (20 and 40%). For the haematological parameters, the total number of erythrocytes, haematocrit, haemoglobin concentration, total leukocytes and total plasma protein had higher values for the treatments with added meal, both 20% and 40%, when compared to the control treatment.